Identification and evaluation of criteria of agile manufacturing using dematel: a case from an indian metal fabrication industry - Bathrinath, S.; Charan, Vadakapur Sai; Ponnambalam, S. G.; Saravanasankar, S. (Penerbit UMP, 2019)
In metal fabrication industry, assembling department plays the major role since it involves risks in assembling the components. Hence, it is always difficult for the manufacturers to identify the criteria of agile manufacturing in assembling department that effects the assembly of the fabricated metal components. Agile manufacturing is one of the innovative method of manufacturing, which focus on the customer satisfaction and also maintaining the quality and cost of the product. Metal fabrication industries generally struggle to find right criteria for better agile manufacturing process. This study focuses on the selection of suitable criteria for agile manufacturing, which requires an in-depth analysis depending on the influence they possess on the agile manufacturing. The objective of this paper is to analyze and identify the most influencing criteria for the metal manufacturing industry based on the customers’ and industrial expert’s perspective. Here we have selected ten different criteria based on the literatures available on the agile manufacturing. The criteria are segregated and ranked according to the nature and influence they possess on other criteria using decision making trial and evaluation laboratory (DEMATEL) methodology. This study also helps the metal fabrication industry to identify the most influencing criteria to implement on agile manufacturing and to have high efficiency on the production. The results show that the customer satisfaction seems to be the primary criteria that will have more influence in metal fabrication industry.